Human behavior from an Islamic perspective: interaction of nature, nurture and spiritual dimension - Abdullah, Fatimah (The International Institute of Islamic Thought, 2011)
Western psychology tends to be divisive in dealing with human personality and has been responsible for the nature-versus nurture controversy. On the one hand, it contends that certain corrupt behavior is predetermined by psychological or biological factors from conception- while on the other, it explains behavior as a simplistic series of reinforcements from contingencies and conditioned responses to environmental stimuli. This secular humanistic outlook has produced an ethical relativism that is the current trend in today's world. This stance is not condemned only by Islam, but also by most religions of the world. This shows that the human nature (fitrah) is still vibrant and dynamic. This article attempts to highlight the importance of the Islamic belief system - which is an integrated and comprehensive way in dealing with human behavior-especially by means of the interaction of nature, nurture, and the spiritual factor in the formation of human behavior.